2012
DOI: 10.1128/aac.05861-11
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Antimicrobial Peptide Subtilosin Acts Synergistically with Glycerol Monolaurate, Lauric Arginate, and ε-Poly- l -Lysine against Bacterial Vaginosis-Associated Pathogens but Not Human Lactobacilli

Abstract: bSubtilosin is a cyclical antimicrobial peptide produced by Bacillus amyloliquefaciens that has antimicrobial activity against the bacterial vaginosis-associated human pathogen Gardnerella vaginalis. The ability of subtilosin to inhibit G. vaginalis alone and in combination with the natural antimicrobial agents glycerol monolaurate (Lauricidin), lauric arginate, and -poly-L-lysine was tested using a checkerboard approach. Subtilosin was found to act synergistically with all of the chosen antimicrobials. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…This result is noteworthy considering that 0.35 mM GML is equivalent to 100 g/ml, and in other studies involving planktonic cells, the MIC of GML was reported to be Ն10 g/ml (3,4,25). Synergistic activity of GML with coenzyme Q1 (26) and lauric arginate (18) has been reported. Thus, using GML in combination with other agents may help combat biofilm drug resistance.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…This result is noteworthy considering that 0.35 mM GML is equivalent to 100 g/ml, and in other studies involving planktonic cells, the MIC of GML was reported to be Ն10 g/ml (3,4,25). Synergistic activity of GML with coenzyme Q1 (26) and lauric arginate (18) has been reported. Thus, using GML in combination with other agents may help combat biofilm drug resistance.…”
mentioning
confidence: 65%
“…2C and D), indicating that GML might facilitate drug inter-action with matrix-embedded bacteria. There is evidence that signal transduction plays a role in GML-mediated inhibition of S. aureus virulence factors, such as beta-lactamase, alpha-hemolysin, and toxic shock syndrome toxin 1 (TSST-1), likely through inhibition of activity at microbial membranes (17)(18)(19). Because we have visual evidence that lipid may be a component of the matrix of S. aureus biofilms (20), it is plausible that GML's role as a surfactant might facilitate matrix penetration, and there is evidence that rhamnolipids and plant biosurfactants have antibiofilm effects (21).…”
mentioning
confidence: 99%
“…The vaginal pathogen (10 8 CFU/ml) was added to the wells (200 l/well) and incubated anaerobically at 37°C for 48 h. Medium alone was used as the positive control and CLI (100 g/ml) as the negative control for growth. Following the incubation period, growth was evaluated by performing viable cell counts using the drop plate method (34,48). Cells were mechanically separated from the hydrogels by making a slit in the hydrogels using a pipette tip.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, bacteriocins have been suggested as potential alternatives to antibiotics for the treatment of BV (31)(32)(33)(34)(35)(36). Unlike broad-spectrum antibiotics, some bacteriocins selectively target pathogenic microorganisms without disturbing the healthy vaginal flora.…”
mentioning
confidence: 99%
See 1 more Smart Citation